Detection and Disposal of Improvised Explosives - Schubert, Hiltmar; Kuznetsov, Andrey; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
The book contains lectures of an international NATO-Russian Advanced Research Workshop about Detection and Disposal of Improvised Explosives used by terrorists. The ARW was an event of a series of workshops before, dealing with detection of explosives by different analytical methods and different shape and compositions of the explosive charge. The formulation "Improvised Explosive", IE, is a new expression for terrorist explosives, which were produced mostly by knowledgeable laymen in a home-made manner. IE can be any chemical compound or mixture of commercial substances, capable of an explosive reaction after initiation by a detonating device. The disposal of such IE is connected with a special danger, because IE are in many cases much more unstable and mechanically more sensitive than commercial or military explosives.
DISPOSAL OF IMPROVISED EXPLOSIVES AND -DEVICES -- DETECTION OF IMPROVISED EXPLOSIVES (IE) AND EXPLOSIVE DEVICES (IED) -- ON-SITE ANALYSIS OF EXPLOSIVES IN VARIOUS MATRICES -- IEDS DETECTION BY EXISTING DETECTION TECHNIQUES -- MICROWAVE SYSTEM FOR INSPECTION OF LUGGAGE AND PEOPLE -- DEVELOPMENT OF METHODS AND EQUIPMENT FOR DETECTION OF EXPLOSIVES' VAPORS IN THE ATMOSPHERE WITH LASER -- DETECTION OF IMPROVISED EXPLOSIVES DEVICES (IED) BY USING TAGGED NEUTRON BEAMS -- SENNA - PORTABLE SENSOR FOR EXPLOSIVES DETECTION BASED ON NANOSECOND NEUTRON ANALYSIS -- LIQUID BLAST INHIBITORS: TECHNOLOGY AND APPLICATION -- RATIONAL DETECTION SCHEMES FOR TATP NATO ADVANCED RESEARCH WORKSHOP -- PEROXIDE EXPLOSIVES -- ASSOCIATED PARTICLE IMAGING: AN ENABLING TECHNOLOGY OF DETECTION OF IMPROVISED EXPLOSIVES -- EXPERIENCE OF APPLICATION OF EXPLOSIVES DETECTORS BY FORENSIC SCIENCE UNITS OF THE MINISTRY OF INTERIOR OF RUSSIAN FEDERATION -- TECHNICAL MASKING OF IMPROVISED EXPLOSIVE DEVICES -- RESEARCH AND DEVELOPMENT ON HUMANITARIAN LANDMINE DETECTION SYSTEM BY A COMPACT DISCHARGE-TYPE D-D FUSION NEUTRON SOURCE -- DETECTION OF NITROAROMATIC DERIVATIVES BY USING REACTIVE ORGANIC THIN LAYERS -- DETECTION OF EXPLOSIVES BY QUADRUPOLE RESONANCE METHOD: NEW ASPECTS FOR SECURITY -- CONCEALED EXPLOSIVES DETECTOR BASED ON PORTABLE NEUTRON GENERATOR -- POSSIBILITIES OF CREATING IMPROVISED EXPLOSIVES AND EXPLOSIVE DEVICES -- INVESTIGATION OF POSSIBILITY TO DETECT THE DETONATORS OF THE EXPLOSIVE DEVICES BY MEANS OF ED XRF APPROACH -- EFFECT/BACKGROUND CORRELATIONS IN NANOSECOND NEUTRON ANALYSIS -- USE OF NON-LINEAR JUNCTION DETECTORS TO ENSURE THE SAFETY OF IED SEARCH.
Keywords: CHEMISTRY; CHEMISTRY, PHYSICAL ORGANIC; WEIGHTS AND MEASURES; CHEMISTRY; PHYSICAL CHEMISTRY; MEASUREMENT SCIENCE, INSTRUMENTATION